IMPLEMENTASI MEDIA INTERAKTIF DALAM MODEL PBL UNTUK MENINGKATKAN LITERASI SISWA KELAS IV A SDN SENDANGMULYO 02 - Elma Nur Santika; Aries Tika Damayani; Sri Wahyuningsih (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This research was motivated by the low literacy skills of class IV A students due to the use of less varied learning models and media, which had an impact on reading interest and low understanding of material concepts. The aim of this research is to examine the impact of implementing interactive media in the Problem Based Learning (PBL) model on increasing the literacy of class IV A students at SDN Sendangmulyo 02. Using a qualitative approach with a case study design, data was collected through interviews, observations and tests. The research results show that through interactive media such as PowerPoint and learning videos, students' literacy can be significantly increased, especially in reading comprehension, writing ability and vocabulary use with an average score increase of 20-30%. In addition, students' critical thinking abilities increased by 34.87%. The use of interactive media also increases students' learning motivation through presenting material that is more interesting and interactive. This research provides evidence that an innovative learning approach with technology integration can improve the literacy skills of class IV A students at SDN Sendangmulyo 02.